2008
DOI: 10.3233/jad-2008-14303
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disease and Hippocampal Atrophy Are Differently Linked to Functional Coupling of Brain Areas: An EEG Coherence Study in MCI Subjects

Abstract: The working hypothesis of paper is that the functional coupling of brain areas is combined with different neuroradiological substrates and has different clinical manifestations. 31 normal old subjects and 85 subjects with mild cognitive impairment (MCI) underwent EEG recordings and magnetic resonance imaging (MRI). Intrahemispheric and interhemispheric linear EEG coherences were computed. At first, all normal old and MCI subjects were compared. Subsequently, three subgroups of MCI were obtained based on neuror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 83 publications
9
46
2
Order By: Relevance
“…Finally, MCIs showed a higher synchronization in the gamma band between right anterior and central areas, which was related to a poorer performance in attention, memory, and executive function, while in the control group, this increase was localized in more posterior regions and was directly correlated with a greater hippocampal volume and higher scores in MMSE, Immediate and Delayed Recall, and Semantic Fluency. Most of these findings, and especially the decrease in synchronization in alpha and beta bands, are in agreement with those found in MCI and AD studies (Berendse et al 2000;Jelic et al 2000;Koenig et al 2005;Stam et al 2003;Moretti et al 2008;Gómez et al 2009), suggesting that MCI could be considered as the beginning of the "disconnection syndrome" (Delbeuck et al 2003). …”
Section: Control Group Vs MCI Groupsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, MCIs showed a higher synchronization in the gamma band between right anterior and central areas, which was related to a poorer performance in attention, memory, and executive function, while in the control group, this increase was localized in more posterior regions and was directly correlated with a greater hippocampal volume and higher scores in MMSE, Immediate and Delayed Recall, and Semantic Fluency. Most of these findings, and especially the decrease in synchronization in alpha and beta bands, are in agreement with those found in MCI and AD studies (Berendse et al 2000;Jelic et al 2000;Koenig et al 2005;Stam et al 2003;Moretti et al 2008;Gómez et al 2009), suggesting that MCI could be considered as the beginning of the "disconnection syndrome" (Delbeuck et al 2003). …”
Section: Control Group Vs MCI Groupsupporting
confidence: 88%
“…For example, Moretti et al (2008) reported a decline in intrahemispheric fronto-parietal coherence and an increase in temporal interhemispheric coherence in the MCI group when compared to elderly controls and also a reduced beta band functional connectivity. Gómez et al (2009) found a decreased synchronization essentially in the beta band in MCI subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Based on such consideration, the DTF connectivity were integrated into 5 frequency bands, i.e. ı (0.5-3.5 Hz), Â (4-7 Hz), ˛1 (8-10 Hz), ˛2 (11)(12)(13) and (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and then statistic tests were performed again. Significant directional connectivity was visualized over the scalp surface using the eConnectome software package [22].…”
Section: Resultsmentioning
confidence: 99%
“…In a study based on coherence analysis with combined EEG and MRI, it was found that MCI patients with subcortical cerebrovascular damage showed a largest decrease in the coherence of fronto-parietal regions in the three MCI subgroups [30]. Another study of resting EEG found that there was a significant correlation between parietal-to-frontal information flow strength and subcortical white matter vascular lesions scores [31].…”
Section: Discussionmentioning
confidence: 97%
“…In the conceptual framework concerning integration of biomarkers for an early and highly predictive diagnosis, the electroencephalogram (EEG) could be a reliable tool 511. Indeed, it is widely accepted that EEG rhythms reflect underlying brain network activity 1216. As a consequence, changes in EEG rhythms could be an early sign of AD.…”
Section: Introductionmentioning
confidence: 99%